Hot to trot [large type] - Beaton, M. C.; Green, R. W. (Novelist) (Beaton, M. C. Agatha Raisin mystery., 2021)
When Agatha Raisin learns that her friend and one-time lover Charles Fraith is to be married to socialite, Miss Mary Brown-Field, she sees it as her duty to find out what she can about the woman. Out of selfless concern for Charles, of course. When Agatha crashes their wedding, it ends in a public altercation. There's a scream from the stable-- and now Agatha and Charles are suspects in a murder. Clues lead to the competitive equestrian world, in which Mary had been enmeshed, where Agatha discovers the victim's surprisingly violent past. -- adapted from jacket and Goodreads info